CONSTRUCTION AND INTERNAL RELIABILITY OF AN ALGORITHM FOR CHOICE CLEANING AND TOPICAL THERAPY ON WOUNDS. - Santos, Aline Caroline; Alves Dutra, Rosimar Aparecida; Magela Salomé, Geraldo; Masako Ferreira, Lydia (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2018)
Objective: to describe the construction and validation of an algorithm with indications of procedures for cleaning and topical wound therapy. Method: this is an analytical, prospective, descriptive study supported by literature review. For the construction of the algorithm, a research was carried out with Health Sciences databases. Thirty health professionals participated as judges in the validation of the algorithm, responding to a questionnaire via e-mail. Results: the judges considered that the algorithm presents information capable of supporting the decision of the professional in the choice of the wound cleaning technique and the therapy. The statistical analysis showed that the issues related to the construction and validation of the algorithm presented excellent reliability, with Cronbach's alpha of 0.962. Conclusion: The validated version of the algorithm based on the literature and validated by health professionals showed statistical reliability for the indication of cleanliness and topical wound therapy.